Zheng Manqing: The Memorial Hall and Legacy of the Master of Five Excellences in Taiwan - Mason, Russ (Revista de Artes Marciales Asiáticas, 2012)
Professor Zheng Manqing (1902-1975), a fine artist and a notable taijiquan disciple of Yang Chengfu, emigrated to Taiwan in 1949 following the Chinese civil war between the Guomindang and Maoist factions. Under Republic of China President Chiang Kai-shek’s Cultural Renaissance Movement, Zheng played an important role in preserving the cultural treasures of traditional China. During the period of Mao Zedong’s Cultural Revolution when the Mainland was veiled to foreign eyes behind the Bamboo Curtain, Zheng was instrumental in introducing taijiquan and other elements of Chinese culture to the West. Zheng passed away at his home in Yonghe, Taiwan in 1975 but not before establishing an international reputation for his mastery in taijiquan and other arts. Recently, a portion of his former residence was converted into a memorial hall (the Zheng Manqing Jinian Guan) by senior students interested in preserving his martial tradition, paintings, calligraphy, and other artifacts. This article provides a brief history of Zheng’s life and his legacy in Taiwan, as well as a photographic tour of the Zheng Manqing Memorial Hall.